2015
DOI: 10.1007/s00464-015-4203-0
|View full text |Cite
|
Sign up to set email alerts
|

Robotic single-site versus laparoscopic cholecystectomy: Which is cheaper? A cost report and analysis

Abstract: In a hospital that has already acquired infrastructure for robotic surgery, we observed procedural costs for RSSC that were lower than LC. This decreased cost was mainly driven by cutting down on supplies (87% of median total cost reduced), and to a lesser extent OR time. A steep learning curve exists after which RSSC OR times can be significantly shortened. A randomized study is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…In our experience, patients undergoing elective surgery for biliary colic or chronic cholecystitis both experienced a decrease in operative time on the robotic platform. These results have been seen by other groups with shorter operative times (18,19). The effect of operative time charges must be included in any cost analysis to accurately assess the impact of this technology.…”
Section: The Cost Of Robotic Surgerymentioning
confidence: 72%
See 1 more Smart Citation
“…In our experience, patients undergoing elective surgery for biliary colic or chronic cholecystitis both experienced a decrease in operative time on the robotic platform. These results have been seen by other groups with shorter operative times (18,19). The effect of operative time charges must be included in any cost analysis to accurately assess the impact of this technology.…”
Section: The Cost Of Robotic Surgerymentioning
confidence: 72%
“…Alternatively, a recent retrospective study of single-site robotic cholecystectomy (SSRC) demonstrated a decrease in median hospital cost ($1,319 SSRC vs. $1,710 LC) (18). Costs were contained by limiting non-essential instruments from standard trays and avoiding disposable items such as a retrieval bag for the specimen.…”
Section: The Cost Of Robotic Surgerymentioning
confidence: 99%
“…In hospitals with an established infrastructure for robotic surgery, there is potential for cost efficacy. In a review from one institution, overall savings from supplies and instruments and shortened operating room times resulted in robotic single-site laparoscopic cholecystectomy being more cost effective than laparoscopic cholecystectomy [53]. When comparing cost margin only at a private community hospital, there was no difference in cost between robotic and laparoscopic cholecystectomy [54].…”
Section: Costmentioning
confidence: 99%
“…The top down analysis found a minimum additional cost of $2,600 per procedure (43) while the instrument price examination found equal instrument costs (19). Two studies found no significant difference (19,44) or minor savings of $391 dollars (45).…”
Section: Analysis Of Rcmentioning
confidence: 99%
“…Similarly, Bedeir et al evaluated 177 robotic and 281 laparoscopic cholecystectomies from 2012 to 2014 (45). The median total costs for RC were significantly lower than the laparoscopic technique (robot: $1,319; laparoscopic: $1,710).…”
Section: Rcmentioning
confidence: 99%